Legal Protection for Copyright Holders against Unauthorized Song Use: A Study of Case Number 92/Pdt.Sus-HKI/Copyright/2024/PN Niaga Jkt.Pst - Rahmawati, Rizki; Asyhadi, Farhan; Rahmatiar, Yuniar (SIGn Jurnal Hukum, 2025)
Copyright protection for musical works is a vital aspect of the music industry. However, the practice of using songs commercially without the creator’s authorization remains a significant problem that violates both economic and moral rights. This research aims to analyze the scope of legal protection for song copyrights under Law Number 28 of 2014 and the challenges of its enforcement. It also critically examines the Panel of Judges’ legal reasoning in Case Number 92/Pdt.Sus-HKI/Copyright/2024/PN Niaga Jkt.Pst concerning the determination of the Performer’s liability and the application of civil sanctions. This normative legal research employs a qualitative analysis of primary and secondary legal materials, drawing on statutory, case, and conceptual approaches. The findings indicate that although Law Number 28 of 2014 provides a robust basis for protection, various enforcement challenges persist. Case Number 92/Pdt.Sus-HKI/Copyright/2024/PN Niaga Jkt.Pst affirmed the occurrence of copyright infringement by the Performer. The ruling found the Performer liable despite the presence of an organizer. It also imposed economic damage sanctions by referencing parameters within criminal provisions. However, the court rejected the claim for moral rights damages for lack of proof. This case has implications for affirming the Performer’s liability and the paradigm for imposing sanctions in song copyright disputes. It also promotes increased legal awareness within the Indonesian music industry.